2004
DOI: 10.2320/matertrans.45.1383
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization of Sn Grains due to Thermal Strain in Sn-1.2Ag-0.5Cu-0.05Ni Solder

Abstract: The formation of fine Sn grains in a Sn-1.2 mass%Ag-0.5 mass%Cu-0.05 mass%Ni solder due to thermal strain was investigated from the viewpoint of recrystallization. After thermal fatigue, small general grains recrystallized at the strain concentrated location in Sn-1.2Ag-0.5Cu-0.05Ni. Through isothermal annealing, however, grains, which had near h110i orientation at a chip-substrate direction before isothermal annealing, coarsened preferentially. Hence, not isothermal annealing but thermal strain was a driving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 15 publications
2
63
0
Order By: Relevance
“…10) In this report, increase in thermal fatigue life due to addition of nickel into Sn-1.2Ag-0.5Cu solder is not resulted from fine Sn grain formation before thermal fatigue but from suppression of Sn grain growth after recrystallization. 10) Figure 11 shows Sn grain mapping with boundaries over (a, d) 15, (b, e) 5 and (c, f) 2 degrees for Sn-1.2Ag-0.5Cu-0.02Ni and Sn-1.2Ag-0.5Cu-0.05Ni solder joints after 600 thermal cycling, respectively. Two large general grains over 100 mm mainly covered 0.02Ni ( Fig.…”
Section: Microstructure After Thermal Fatiguementioning
confidence: 72%
“…10) In this report, increase in thermal fatigue life due to addition of nickel into Sn-1.2Ag-0.5Cu solder is not resulted from fine Sn grain formation before thermal fatigue but from suppression of Sn grain growth after recrystallization. 10) Figure 11 shows Sn grain mapping with boundaries over (a, d) 15, (b, e) 5 and (c, f) 2 degrees for Sn-1.2Ag-0.5Cu-0.02Ni and Sn-1.2Ag-0.5Cu-0.05Ni solder joints after 600 thermal cycling, respectively. Two large general grains over 100 mm mainly covered 0.02Ni ( Fig.…”
Section: Microstructure After Thermal Fatiguementioning
confidence: 72%
“…[5][6][7][8][9][10] A modification of the conventional dye-and-pry technique allowed the measurement of very small fatigue cracks and, contrary to popular belief, the crack initiation stage was found to be negligible in thermal cycling. 11 Crack growth did, however, remain quite limited until a continuous network of high-angle grain boundaries had been established across the high-strain region in the joint.…”
Section: Damage and Failurementioning
confidence: 99%
“…1 are not preferred paths for crack propagation. Instead, failure in thermal cycling almost always occurs by recrystallization of the Sn to form a network of high-angle grain boundaries across the joint [5][6][7][8][9][10] , followed by cracking along these boundaries. [11][12][13] It is our belief that the general picture below can be extended to explain the superior performance of a so-called interlaced twinning structure, 14 but that may require more work.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when stress is applied to interconnections having this kind of microstructure, they undergo microstructural evolution before fractures can propagate. Investigations of the microstructures of failed solder interconnections have indicated that the microstructures formed during solidification are not stable and will change notably during the operation of products [15,17,18,[56][57][58][59][60][61][62][63].…”
Section: As-solidified Microstructures Of Tin-rich Solder Interconnecmentioning
confidence: 99%
“…Because recovery and recrystallization are competing processes, the progress of recovery can reduce the driving force of recrystallization significantly and recrystallization may not always initiate. On the other hand, it is well documented that neareutectic SnAgCu interconnections do recrystallize under dynamic loading caused by changes in temperature (between -45 ºC and +125 ºC), as well as under power cycling conditions (between room temperature and +125 ºC) [15,17,18,[56][57][58][59][60][61][62][63]73]. Thus, it seems that near-eutectic SnAgCu solder interconnections recrystallize only under restricted loading conditions: dynamic loading conditions where the strain hardening is more effective than the recovery.…”
Section: Restoration Of Tin-rich Solder Alloysmentioning
confidence: 99%